Pengaruh Konsumsi Nugget Tahu Daun Kelor terhadap Peningkatan Berat Badan Balita - Septiana, Efa; Niken Kartika Sari; Fahrul Irayani (Poltekkes Kemenkes Kupang, 2025)
Background: Nutrition is an important factor that supports children's growth and development. Malnutrition remains a serious problem among toddlers, characterized by weight below the age-standard (weight-for-age, W/A), which can affect physical growth, cognitive development, and overall health. One potential strategy is the provision of moringa leaf tofu nuggets, which are rich in protein and essential micronutrients for children. Objective: To determine the effect of consuming moringa leaf tofu nuggets on the weight gain of toddlers aged 24–60 months at KB Ummul Quro, Central Lampung Regency. Method: Pre-experimental research, with one group pretest-posttest design. The study sample consisted of 20 toddlers who were BGK and BGM on the growth chart, using a total sampling technique. Data were analyzed using the Paired Sample T-Test. Results: The average weight of toddlers increased from 10.4 kg before the intervention to 10.7 kg after 30 days of consuming moringa leaf tofu nuggets. The statistical test showed a p-value of 0.000 < 0.05, indicating that H0 was rejected and Ha accepted. This demonstrates that providing moringa leaf tofu nuggets has a significant effect on increasing the weight of toddlers.